2009
DOI: 10.1007/s00586-009-1051-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel computer-assisted drill guide template for placement of C2 laminar screws

Abstract: The present method of C2 laminar screw placement relies on anatomical landmarks for screw placement. Placement of C2 laminar screws using drill template has not been described in the literature. The authors reported on their experience with placement of C2 laminar screws using a novel computer-assisted drill guide template in nine patients undergoing posterior occipitocervical fusion. CT scan of C2 vertebrae was performed. 3D model of C2 vertebrae was reconstructed by software MIMICS 10.01. The 3D vertebral mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 31 publications
0
83
0
7
Order By: Relevance
“…The data from general population may not apply to patients with OO. In addition, the use of C2 laminar screws in atlantoaxial fixation in attempt to reduce the risk for the vertebral artery (VA), was first reported by Wright et al [36] in 2004 and since became popular [18,19,38]. For OO patients, however, a couple of questions arise: can C2 pedicle screw be safely placed in every OO patient?…”
Section: Introductionmentioning
confidence: 99%
“…The data from general population may not apply to patients with OO. In addition, the use of C2 laminar screws in atlantoaxial fixation in attempt to reduce the risk for the vertebral artery (VA), was first reported by Wright et al [36] in 2004 and since became popular [18,19,38]. For OO patients, however, a couple of questions arise: can C2 pedicle screw be safely placed in every OO patient?…”
Section: Introductionmentioning
confidence: 99%
“…The concept of personalized image-based 3D templates was first described by Berry et al 4 Owen et al and Ryken and colleagues followed the concept with their cadaveric studies, 25,29,30 and then Lu and colleagues [16][17][18] and Kawaguchi et al 12 applied the templates for clinical use as drill guide templates. However, these templates were only used as a drilling guide.…”
Section: Discussionmentioning
confidence: 99%
“…The use of intra-operative imaging increases harmful radiation exposure for both doctors and patients (30,(34)(35)(36). 3DP guides may offer an alternative as a simple, convenient, low cost and complexequipment free way to improve the accuracy of pedicle screw placement (30)(31)(32)(33)(34)(35)(36)(37)(39)(40)(41)(42)(43).…”
Section: Surgical Guidesmentioning
confidence: 99%
“…Next, a 3D model is generated by specialist software from which the optimal screw trajectory and size can be determined, often in consultation with the surgeon. Finally, a navigational template is designed and built with optimal screw trajectory, the surface of which is the inverse of the posterior vertebral surface to ensure a good fit and accuracy of screw insertion (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)55). Numerous studies demonstrated that the guides help to lower operation time, with Deng et al (37) suggesting this may decrease complications related to operative time (e.g., infection) (30,35,37,43).…”
Section: Surgical Guidesmentioning
confidence: 99%
See 1 more Smart Citation